Clinical and virological features of acute hepatitis E in Gunma prefecture, Japan between 2004 and 2015. Issue 5 (27th July 2016) - Yamazaki, Yuichi; Naganuma, Atsushi; Arai, Yosuke; Takeuchi, Suguru; Kobayashi, Takeshi; Takakusagi, Satoshi; Hatanaka, Takeshi; Hoshino, Takashi; Namikawa, Masashi; Hashizume, Hiroaki; Takizawa, Daichi; Ohyama, Tatsuya; et al.
Abstract : Aim: To evaluate the clinical and virological features of acute hepatitis E (AH‐E) in Gunma prefecture and focus on the hepatitis E virus (HEV) infection in immunocompromised patients. Methods: A total of 30 patients with AH‐E diagnosed at our Gunma University Hospital, and located in 3‐39‐15 Showa‐machi, Maebashi, Gunma 371‐8511 Japan, and its affiliated hospitals from 2004 to 2015, were studied. We evaluated the detailed medical histories, laboratory examinations and virological features of these participants. Results: Of the 30 patients, 21 patients were men, with a median age of 61 years. Three of these patients had a history of recent oversea travel. A total of 14 patients had eaten raw or undercooked meat/viscera from animals, and two patients had contracted transfusion‐transmitted AH‐E. Eight patients were immunocompromised, including those with hematological disease, cancer receiving systemic chemotherapy and kidney transplant or connective tissue disease undergoing immunosuppressive medications. The alanine aminotransferase and total bilirubin levels were more significantly reduced in these immunocompromised patients than in the non‐immunocompromised patients. Severe thrombocytopenia, an extra‐hepatic manifestation of AH‐E, occurred in one case. Among the 22 HEV strains whose subgenotype was determined, two were imported strains (1a and 1f), and 11 strains formed four distinct phylogenetic clusters within subgenotype 3b. The remaining nine strains differed from each other by 9.8–22.4%, and were classified into four subgenotypes (3a, 3b, 3e and 3f). Conclusion: Markedly divergent HEV strains (3a, 3b, 3e and 3f) were found to circulate in Gunma. Although immunosuppression appears to play a crucial role in establishing chronic sequels, AH‐E in eight immunocompromised patients, including transfusion‐transmitted HEV infection in two patients, did not become chronic.